Breast Cancer Clinicopathology Based on Neutrophil Levels at Adam Malik Hospital Medan in 2018–2021 - Tonggo Mario Saragih; Dedy Hermansyah; Denny Rifsal Siregar; Dina Aprillia Ariestine (Talenta Publisher, 2024)
Background: Breast cancer is the most frequently diagnosed cancer in the world. Breast cancer occurs due to abnormal cell growth in breast tissue so that it becomes malignant. In Indonesia, breast cancer is the most common cancer in women. That way, many markers are needed as prognostic and predictive of breast cancer. One of the prognostic factors for breast cancer is neutrophil levels combined with clinicopathological factors. Objective: Knowing the clinicopathology of breast cancer based on neutrophil levels at the Adam Malik Medan General Hospital in 2018-2021. Methods: The research design is observational with a descriptive method and calculated using the Lemeshow formula. Results: Majority aged 40-49 years (39.6%), high school (44.8%), housewives (67.7%), no family history (97.9%), tumor grade II (38.5%) %), Tumor Infiltrating Lymphocytes (TILs) severe (47.9 %), mitotic score 1 (38.5 %), metastatic positive lymph node status (87.5 %), tumor size T1 (36.5 %), The number of positive and negative Estrogen Receptors is the same (50.0%). Conclusion: High levels of neutrophils tend to result in severe Tumor Infiltrating Lymphocytes (TILs) which will increase tumor growth, occurrence of metastases, increased positive angioinvasion, negative Estrogen Receptor status, negative Progesterone Receptor status, HER2 1+ status, positive Ki-67 status.